Mild hypothermia effects on serum neuroprotection, nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and superoxide dismutase (SOD) levels in neonates with hypoxic-ischemic encephalopathy - Duan Wenfeng; Wang Xuan (Journal of Medical Biochemistry, 2025)
Background: Neonatal hypoxic-ischemic encephalopathy (HIE) is a serious condition that can lead to long-term neurological damage. Mild hypothermia is a promising treatment for HIE, but its efficacy and safety in newborns are not well established. To evaluate the therapeutic effects of mild hypothermia on neonatal HIE in a randomised controlled trial. Methods: This was a prospective study of 132 newborns with HIE treated with either mild hypothermia or routine conventional treatment. The primary outcome measures were changes in neural cytokines, brain injury markers, oxidative stress factors, neurological function recovery time, and therapeutic outcomes. Results: The mild hypothermia group showed significant improvements in neural cytokines (NGF and BDNF), brain injury markers (S100B, NSE, and MBP), and oxidative stress factors (SOD, MDA, IL-18, and caspase-3) compared to the control group. The mild hypothermia group also had a faster neurological function recovery time and a higher total response rate (95.45% vs. 80.30%, P<0.05) compared to the control group. Conclusions: Mild hypothermia therapy is a safe and effective treatment for neonatal HIE, with significant improvements in neural cytokines, brain injury markers, and oxidative stress factors, as well as faster neurological function recovery time and higher therapeutic outcomes. Results: The mild hypothermia group showed significant improvements in neural cytokines (NGF and BDNF), brain injury markers (S100B, NSE, and MBP), and oxidative stress factors (SOD, MDA, IL-18, and caspase-3) compared to the control group. The mild hypothermia group also had a faster neurological function recovery time and a higher total response rate (95.45% vs. 80.30%, P<0.05) compared to the control group. Conclusions: Mild hypothermia therapy is a safe and effective treatment for neonatal HIE, with significant improvements in neural cytokines, brain injury markers, and oxidative stress factors, as well as faster neurological function recovery time and higher therapeutic outcomes. The novelty of this work was that it showed potential biomarkers for evaluating response to treatment and the pathophysiological effect of treatment by assessing these biomarkers.